Pengaruh Inovasi Teknologi dan Kualitas Layanan Dinas Perpustakaan dan Kearsipan Provinsi Bengkulu Terhadap Kepuasan Pemustaka - Gunaidi, Aang; Utama, Sarah Mentari; Agusten, Andre (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The implementations of information technology in the library field have positive impact not only for librarians as library directors but for visitors as library users. Bengkulu’s Library Service innovates library services by presenting digital library through an application called